2012
DOI: 10.1134/s0006297912070073
|View full text |Cite
|
Sign up to set email alerts
|

The phenoptosis problem: What is causing the death of an organism? Lessons from acute kidney injury

Abstract: Programmed execution of various cells and intracellular structures is hypothesized to be not the only example of elimination of biological systems - the general mechanism can also involve programmed execution of organs and organisms. Modern rating of programmed cell death mechanisms includes 13 mechanistic types. As for some types, the mechanism of actuation and manifestation of cell execution has been basically elucidated, while the causes and intermediate steps of the process of fatal failure of organs and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Although acute tubular necrosis is characteristic of most intrinsic AKI, surprisingly limited histological evidence of injury was found despite severe organ failure (11). Zorov et al (161) believe that it is the immune system involved in mitochondrial signaling, and not kidney failure itself, that leads to an organism's senescence and death. Recent reviews have highlighted the critical role of sublethal hypoxic tubular cell injury and microcirculation disturbance in the pathogenesis of AKI (2,57).…”
Section: Acquired Mitochondrial Dysfunction In Kidney Diseasementioning
confidence: 99%
“…Although acute tubular necrosis is characteristic of most intrinsic AKI, surprisingly limited histological evidence of injury was found despite severe organ failure (11). Zorov et al (161) believe that it is the immune system involved in mitochondrial signaling, and not kidney failure itself, that leads to an organism's senescence and death. Recent reviews have highlighted the critical role of sublethal hypoxic tubular cell injury and microcirculation disturbance in the pathogenesis of AKI (2,57).…”
Section: Acquired Mitochondrial Dysfunction In Kidney Diseasementioning
confidence: 99%
“…Whereas oxidative stress can be easily assessed in a cell culture setting, including the extent of ROS generation and ROS-induced cell death, it is still unclear how this can be translated into a whole organism setting. Large amounts of data and arguments about the mechanisms of cell death have been collected, while at the same time our understanding of the causes of failure of functioning of an entire organ or an organism and the role ROS may play in this, is fragmentary and incomplete [57]. Although it is not known exactly how the results from cell culture studies can be translated to organisms, interesting connections can be seen between social stress and biological aging mechanisms.…”
Section: Pathophysiological Role Of Stressmentioning
confidence: 96%
“…Recently, mitochondria-targeted antioxidants, which carry both antioxidative properties and the ability to be accumulated in the mitochondria of cells, have become available. A comprehensive investigation of the effect of mitochondrial antioxidants from the SkQ family on renal pathologies demonstrated that SkQ1 introduced one day before I/R prevented the animals' death [97], and the administration of SkQ1 3 hour before and 1 hour after ischemia and every 12 hours during the post-ischemic period for 2 days improved kidney function [98]. An even more pronounced nephroprotective potential was reported for SkQR1.…”
Section: Mitochondrial Antioxidantsmentioning
confidence: 99%